A Nano-Traditional Chinese Medicine Against Lymphoma That Regulates the Level of Reactive Oxygen Species - Zhao, Qiangqiang; Li, Jian; Wu, Bin; Shang, Yinghui; Huang, Xueyuan; Dong, Hang; Liu, Haiting; Gui, Rong; Nie, Xinmin (Frontiers in Chemistry, 2020)
Jolkinolide B (JB) is a bioactive compound isolated from a Chinese herbal medicine that exerts antitumor activity. However, the anti-lymphoma effect of JB and its mechanism are yet to be revealed. Because free JB has poor pharmacokinetics and weak antitumor efficacy, we opted to use black phosphorus quantum dot (BPQD) nanomaterials as a drug loading platform to synthesize a nano-traditional Chinese medicine (nano-TCM) called BPQDs@JB. Compared with free JB, Raji cells administrated with BPQDs@JB exhibited the cell viability of 19.85±1.02%, and the production of intracellular reactive oxygen species (ROS) was promoted. Likewise, BPQDs@JB was capable of rising the apoptosis rate of Raji cells to 34.98±1.76%. In nude mice transplanted tumor model administrated with BPQDs@JB, the tumor tissue sections administrated with BPQDS@JB achieved a conspicuous red fluorescence, demonstrating the presence of most ROS production in the BPQDS@JB. TUNEL achieved a number of positive (brown) nuclei in vivo, revealing that BPQDS@JB could significantly induce tumor tissue apoptosis. As revealed from the mentioned results, BPQDs@JB can generate considerable ROS and interfere with the redox state to inhibit tumor. In brief, BPQDs@JB may be adopted as a treatment option for lymphoma.